2020
DOI: 10.21203/rs.3.rs-30320/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development of significant disease in a cohort of patients with non-specific enteritis on capsule endoscopy. Clinical suspicion and a high base line Lewis score are predictive of Crohn’s disease.

Abstract: Background: As with isolated ileitis the findings of nonspecific small bowel enteritis (NSE) on capsule endoscopy (CE) poses a clinical challenge. There is lack of available evidence to help clinicians to predict significant disease and long-term prognosis. Methods: We aimed to define the natural history of NSE in an Irish cohort. Patients with a finding of NSE were identified from a database. Subsequent investigations, treatments and diagnosis were recorded. Patients were grouped based on ultimate diagnosis: … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…A retrospective observational study by Freitas et al 97 investigated 102 patients found to have “isolated terminal ileitis” at ileocolonoscopy, endoscopic abnormalities proximal to the terminal ileum were found in 36.3 % of patients; one third (35/102) were finally diagnosed with CD. Similarly, isolated ileitis on SBCE can frequently herald an ultimate diagnosis of CD, even in patients with an initial negative ileocolonoscopy 98 99 .…”
Section: Crohn’s Diseasementioning
confidence: 99%
“…A retrospective observational study by Freitas et al 97 investigated 102 patients found to have “isolated terminal ileitis” at ileocolonoscopy, endoscopic abnormalities proximal to the terminal ileum were found in 36.3 % of patients; one third (35/102) were finally diagnosed with CD. Similarly, isolated ileitis on SBCE can frequently herald an ultimate diagnosis of CD, even in patients with an initial negative ileocolonoscopy 98 99 .…”
Section: Crohn’s Diseasementioning
confidence: 99%